KANDUNGAN KALSIUM PADA AIR SUMUR YANG DIKONSUMSI PARA PENDERITA PENYAKIT BATU GINJAL DI KECAMATAN RATATOTOK KABUPATEN MINAHASA TENGGARA - Sumampouw, Oksfriani J. (Jurnal Biomedik : JBM, 2010)
Abstract: Kidney stones affect 12% of the American population. Fifty percent (50%) of people treated for kidney stones will have recurrences within 10 years. Calcium oxalate accounts for 90% of the kidney stone incidences. The soil structure of the Ratatotok area contains a lot of lime stone; therefore, the calcium content of well water there is estimated to be high. In fact many people in the South-East Minahasa region, particularly the Ratatotok District, use well water as a drinking water supply; therefore, they have a tendency to get kidney stones. This is an analytical explorative research using 25 respondents and the well water in Ratatotok. We used a descriptive exploratory method. In this research there were primary and secondary data. The primary data, the calcium content, were taken with a purposive method from the 25 wells used by the 25 kidney stone patients. The secondary data were taken from the 25 patients’ questionnaires. The calcium content was analyzed in a laboratory by using a spectrophotometer. Respondents’ characteristics were analyzed descriptively by using the SPSS version 16.0 for data counting. This research reported that 1) the majority of kidney stone patients in Ratatotok, South East Minahasa were male of 45-54 years old with an average age of 49.64 years, 2) all of the calcium contents of the well water consumed by the kidney stone patients at Ratatotok, South East Minahasa were higher than the maximum standard (10 ppm). The conclusion of this research was that the well water consumed by the kidney stone patients in the Ratatotok District, South East Minahasa had a higher level of calcium than the maximum standard for it. Key words: Ratatotok, calcium content, well water, kidney stone. Abstrak: Batu ginjal terjadi pada 12% masyarakat Amerika. Lima puluh persen (50%) dari penderita batu ginjal yang telah memperoleh pengobatan akan kembali mengalaminya dalam 10 tahun. Kalsium oksalat merupakan 90% penyebab insiden batu ginjal. Struktur tanah daerah Ratatotok banyak mengandung batu gamping atau kapur sehingga diperkirakan kandungan kapur dalam air sumur cukup tinggi. Masyarakat di Kecamatan Ratatotok Kabupaten Minahasa Tenggara banyak menggunakan air sumur sebagai sumber air minum sehingga berpeluang menderita batu ginjal. Metodologi yang digunakan ialah deskriptif eksploratif. Data yang diperoleh merupakan data primer dan sekunder. Data primer yaitu kadar kalsium diambil secara purposive pada 25 sumur yang digunakan oleh penderita batu ginjal dan data sekunder diperoleh dari 25 penderita batu ginjal yang telah didiagnosis menggunakan kuesioner. Kadar kalsium diukur menggunakan spektro-fotometer. Karakteristik responden diolah menggunakan SPSS versi 16.0. Dari penelitian ini diperoleh bahwa: 1) penderita batu ginjal di Ratatotok Minahasa Tenggara paling banyak berjenis kelamin laki-laki berumur 45-54 tahun dengan rata-rata umur 49,64 tahun, 2) Kandungan kalsium air sumur yang dikonsumsi oleh para penderita batu ginjal sudah berada di atas standar kualitas air minum. Kesimpulan dari penelitian ini yaitu air sumur yang dikonsumsi para penderita batu ginjal di Kecamatan Ratatotok Kabupaten Minahasa Tenggara mempunyai kadar kalsium di atas standar kualitas air minum. Kata Kunci: Ratatotok, kandungan kalsium, air sumur, batu ginjal.